Characterization of an additively manufactured coating using an upsetting test with miniaturized cylindrical specimen - März, Raphaela; Hetz, Peter; Bartels, Dominic; Schmidt, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2024)
In order to reduce CO2 emissions in production industry, the combination of several manufacturing processes is coming to the fore. One example is the combination of metal additive manufacturing with the forming technology, whereby the advantages of both process technologies can be used. The process combination can be applied to produce hybrid barrel sleeves, for example. Using a laser-based directed energy deposition (DED-LB/M), a circular coating is first applied to a blank, which is then deep-drawn in a second step. The additive layer serves as a wear-resistant coating. One way to increase process understanding for this process combination is numerical simulation. An important part of setting up the simulation model is characterizing the material in terms of its mechanical behavior. In order to avoid long building times, small sample geometries are suitable for characterizing the additive material. In the context of the paper, the upsetting test is therefore carried out with miniaturized specimens, whereby not only the base material Bainidur AM but also the addition of tungsten carbide microparticles and carbon nanoparticles is investigated. The in-situ modification of the material significantly increases the yield strength, but at the same time reduces the ductility. The microhardness of the material is also increased by the addition of carbon or tungsten carbid
Keywords: DED-LB/M; hybrid parts; material characterization